Adhesive composition and polarizing plate using the same

The adhesive composition with hydroxyl group-containing (meth)acrylate and isocyanate compounds addresses the issue of adhesive failure and discoloration in polarizing plates, ensuring high durability and adhesion in harsh environments.

JP2025007963APending Publication Date: 2025-01-20NIPPON KAYAKU CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023109730
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Conventional adhesive compositions used for bonding protective films to polarizers in liquid crystal display devices fail to maintain adhesive strength and prevent peeling under high temperature and high humidity conditions, leading to potential discoloration and detachment of the polarizer.

Method used

An adhesive composition containing specific amounts of hydroxyl group-containing (meth)acrylate and isocyanate compounds, without using an acid generator, is used to bond protective films to polyvinyl alcohol resin films, ensuring high adhesive strength and durability even in harsh environments.

Benefits of technology

The adhesive composition provides sufficient adhesive strength and durability to the polarizing plate, preventing peeling and discoloration of the polarizer under high temperature and high humidity conditions, while maintaining optical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007963000001
    Figure 2025007963000001
  • Figure 2025007963000002
    Figure 2025007963000002
  • Figure 2025007963000003
    Figure 2025007963000003
Patent Text Reader

Abstract

To provide a polarizing plate capable of preventing a coloration in a polarizing plate by turning into polyene when exposed under a high-temperature environment, and also capable of preventing a separation between a protective film and a polarizing plate bonded interposing an adhesive agent, even under a high-temperature high-humidity environment.SOLUTION: An adhesive agent is to be used for bonding a protective film and a polarizing plate including a polyvinyl alcohol resin film with iodine or dichromatic dye absorbed and oriented. Based on adhesive composition 100 pts.mass, (a) hydroxy group-containing (meth)acrylate is included by 25 wt.% to 65 wt.%, inclusive, and (b) isocyanate compound is included by more than 20 wt.% to 70 wt.% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition having high resistance to high temperatures and high humidity and adhesiveness, and to a polarizing plate obtained by laminating a protective film on one or both sides of a polarizer using the adhesive composition. [Background technology]

[0002] In recent years, the applications of various liquid crystal display devices have expanded to include not only mobile devices such as mobile phones and tablet terminals, but also in-vehicle image display devices such as car navigation devices and rear monitors. Accordingly, the image display devices are required to have higher durability in harsher environments (for example, high-temperature environments) than has been conventionally required.

[0003] Polarizing plates are useful as one of the optical components that constitute liquid crystal display devices. Polarizing plates usually have a structure in which protective films are laminated on both sides of a polarizer, and are incorporated into liquid crystal display devices for use. Until now, triacetyl cellulose films have been used for many of the protective films. Triacetyl cellulose has high moisture permeability, and polarizing plates to which it is attached as a protective film have problems such as deterioration under conditions of moist heat, for example, a temperature of 85°C and a relative humidity of 85%.

[0004] In view of this, a method has been proposed to solve this problem by using a resin film having a lower moisture permeability than a triacetyl cellulose resin film as a protective film, and for example, it is known to use an amorphous polyolefin resin as a protective film. Specifically, Patent Document 1 describes laminating a thermoplastic saturated norbornene resin sheet as a protective film on at least one surface of a polarizer.

[0005] When such a protective film having low moisture permeability is laminated using a conventional device, so-called wet lamination, in which an adhesive containing water as the main solvent, for example, an aqueous polyvinyl alcohol solution, is used to laminate the protective film to a polyvinyl alcohol-based polarizer and then the solvent is dried, has problems such as insufficient adhesive strength being obtained and poor appearance, etc. This is because films having low moisture permeability are generally more hydrophobic than triacetyl cellulose films and the low moisture permeability means that water, which is the solvent, cannot be sufficiently dried.

[0006] In view of this, Patent Document 2 discloses an adhesive whose main component is an epoxy resin that does not contain an aromatic ring, and proposes an adhesion method that uses cationic polymerization by heating or irradiation with active energy rays. However, although these adhesives improve adhesive strength due to the effect of the generated cations, there is a problem that the polarizer turns brown due to polyenization during durability tests.

[0007] Furthermore, Patent Document 3 discloses an adhesive using a hydroxyl group-containing acrylate and an isocyanate compound. Since this adhesive composition does not use an acid, discoloration of the polarizer due to polyenation can be prevented. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 6-51117 [Patent Document 2] JP 2004-245925 A [Patent Document 3] JP 2010-8928 A

[0009] Summary of the Invention [Problem to be solved by the invention]

[0010] However, the adhesive composition described in Patent Document 3 has a problem in that the protective film and the polarizer attached via the adhesive peel off from each other in a high-temperature and high-humidity environment.

[0011] An object of the present invention is to provide a polarizing plate in which coloring of the polarizer due to polyenation does not occur when exposed to a high-temperature environment, and in which the protective film and polarizer attached via an adhesive do not peel off from each other even in a high-temperature and high-humidity environment. [Means for solving the problem]

[0012] As a result of intensive research, the present inventors have found that by laminating a polarizer and a protective film with an adhesive composition that does not use an acid generator and that contains specific amounts of a hydroxyl group-containing (meth)acrylate and an isocyanate compound as essential components, the adhesive composition maintains adhesion even under high temperature and high humidity conditions and prevents a polarizer made of a polyvinyl alcohol-based resin film from being discolored, thereby completing the present invention. That is, the present invention relates to the following [1] to [6].

[0013] [1] An adhesive used for bonding a polarizer made of a polyvinyl alcohol-based resin film having iodine or a dichroic dye adsorbed and oriented thereon and a protective film, the adhesive composition comprising: (a) 25% by weight or more and 65% by weight or less of a hydroxyl group-containing (meth)acrylate; and (b) isocyanate compounds are more than 20% by weight and not more than 70% by weight; An adhesive composition comprising: [2] The adhesive composition according to the above item [1], further comprising a photopolymerization initiator. [3] The adhesive composition according to the above item [1] or [2], wherein the isocyanate compound is at least one selected from the group consisting of an isocyanurate of hexamethylene diisocyanate, an adduct of hexamethylene diisocyanate, and a biuret of hexamethylene diisocyanate. [4] The adhesive composition according to the above item [1] or [2], further comprising a urethane acrylate. [5] A polarizing plate comprising a protective film attached to one or both sides of a polyvinyl alcohol-based resin film having iodine or a dichroic dye adsorbed and oriented thereon, using the adhesive composition described in the preceding item [1] or [2]. [6] The polarizing plate according to item [5] above, in which a film of at least any one transparent resin selected from the group consisting of amorphous polyolefin-based resins, polyester-based resins, acrylic-based resins, polycarbonate-based resins, polysulfone-based resins, and alicyclic polyimide-based resins is bonded to at least one surface of the polarizer as the protective film. Effect of the Invention

[0014] By producing a polarizing plate using the adhesive composition of the present invention, the protective film and the polarizer have sufficient adhesive strength, and the polarizing plate can ensure high durability even in a high-temperature and high-humidity environment.

[0015] Hereinafter, embodiments according to the present invention will be described in detail. Note that the following embodiments are examples of some representative embodiments of the present invention, and various modifications can be made within the scope of the present invention.

[0016] [Adhesive composition] The adhesive composition of the present invention is an adhesive used for bonding a polarizer made of a polyvinyl alcohol-based resin film having iodine or a dichroic dye adsorbed and oriented thereon to a protective film, and is characterized by containing a hydroxyl group-containing (meth)acrylate and an isocyanate compound as essential components.

[0017] The adhesive composition is characterized in that it contains, relative to 100 parts by weight of the composition, (a) 25% by weight or more and 65% by weight or less of a hydroxyl group-containing (meth)acrylate, and (b) more than 20% by weight and 70% by weight or less of an isocyanate compound. The adhesive can contain, as necessary, a radical polymerization component (c) and a photoradical polymerization initiator (d) as adhesive components.

[0018] The (a) hydroxy group-containing (meth)acrylate contained in the adhesive composition of the present invention is a (meth)acrylate having one or two acryloyl groups each having a hydroxy group, and specifically, 2-hydroxyethyl (meth)acrylate or 1-hydroxyethyl (meth)acrylate or 2-hydroxypropyl (meth)acrylate or 3-hydroxypropyl (meth)acrylate or 1-hydroxypropyl (meth)acrylate or 4-hydroxybutyl (meth)acrylate or 3-hydroxybutyl (meth)acrylate or 2-hydroxybutyl (meth)acrylate. At least one selected from the group consisting of 1-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, N-(2-hydroxyethyl) (meth)acrylamide, 1,6-hexanediylbis[oxy(2-hydroxy-3,1-propanediyl)]bisacrylate, isocyanuric acid EO-modified di(meth)acrylate, 1-(acryloyloxy)-3-(methacryloyloxy)-2-propanol, glycerol di(meth)acrylate, etc. The hydroxyl group-containing (meth)acrylate is an essential component not only for increasing the adhesive strength as an adhesive, but also for reducing the viscosity of the adhesive composition and improving the applicability to the protective film. Furthermore, the hydroxyl groups of these hydroxyl group-containing (meth)acrylates react with the isocyanate groups of the (b) isocyanate compound to form an adhesive layer with high crosslinking density, making it possible to provide a polarizing plate with high adhesive strength and excellent durability. Among the hydroxyl group-containing (meth)acrylates, an appropriate combination of hydroxyl group-containing (meth)acrylates in which the alkyl group has 2 to 6 carbon atoms is suitable for adjusting the wettability of the coating liquid with the polarizing film or protective film and the plasticity of the cured product after photocuring, and in particular, 4-hydroxybutyl acrylate with 4 carbon atoms is particularly preferred from the viewpoint of film processing, since it can increase the adhesion immediately after curing.Furthermore, when a (meth)acrylate containing two or more hydroxy groups is added to the adhesive composition, the crosslinking density increases, thereby improving durability. However, the viscosity of the adhesive composition increases rapidly over time, so it is preferable to add the (meth)acrylate in an amount of 50% by weight or less.

[0019] The content of the hydroxyl group-containing (meth)acrylate is preferably 25% by weight or more and 65% by weight or less, more preferably 30% by weight or more and 60% by weight or less, and even more preferably 35% by weight or more and 55% by weight or less, based on 100 parts by weight of the adhesive composition. If the content of the hydroxyl group-containing (meth)acrylate is less than 25% by weight, the adhesiveness is reduced and peeling may occur at the interface between the polarizer and the protective film. If the content is more than 65% by weight, the crosslink density of the adhesive layer after curing is low and durability may decrease.

[0020] By adding the isocyanate compound (b) contained in the adhesive composition of the present invention, the isocyanate group reacts with the hydroxy group of the polyvinyl alcohol used in the polarizer, thereby exhibiting high adhesion, and also reacts with the hydroxy group of the hydroxy group-containing (meth)acrylate, thereby increasing the crosslink density and exhibiting high durability.

[0021] Specifically, the isocyanate compound is 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate, 1,5-naphthalene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 3,3'-dimethylphenylene diisocyanate, 4,4'-biphenylene diisocyanate, 1,6-hexane diisocyanate, isophorone diisocyanate, Examples of isocyanate include methylene bis(4-cyclohexyl isocyanate), 2,2,4-trimethylhexamethylene diisocyanate, bis(2-isocyanate ethyl) fumarate, 6-isopropyl-1,3-phenyl diisocyanate, 4-diphenylpropane diisocyanate, lysine diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, tetramethyl xylylene diisocyanate, 2,5 (or 6)-bis(isocyanate methyl)-bicyclo[2.2.1]heptane, and acryloyl alkyl isocyanate. Polyisocyanates, which are modified isocyanates, can also be used, and specific examples include adducts, isocyanurates, biurets, and allophanates, which are modified with polyhydric alcohols such as trimethylolpropane and pentaerythritol.

[0022] Among these, it is particularly preferable to combine at least one selected from 1,6-hexane diisocyanate isocyanurate, 1,6-hexane diisocyanate adduct, and 1,6-hexane diisocyanate biuret. Specific product names include Duranate 24A-100, Duranate TPA-100, and Duranate E402-100 manufactured by Asahi Kasei Corporation.

[0023] The content of the isocyanate compound is preferably more than 20% by weight and less than 70% by weight, more preferably more than 30% by weight and less than 65% by weight, and even more preferably 40% by weight and less than 60% by weight, based on 100 parts by weight of the adhesive composition. If the content of the isocyanate compound is less than 20% by weight, the adhesiveness decreases due to the small number of isocyanate groups. In addition, with the decrease in crosslink density, the polarizer peels off from the protective film and shrinks in a durability test, and the state where only the protective film remains at the end is visually observed. If the content is more than 70% by weight, the crosslink density of the adhesive layer also decreases, so that durability may decrease, and the viscosity of the adhesive composition increases rapidly over time, making it unsuitable for processability.

[0024] The adhesive composition of the present invention may contain a radical polymerization component (c) as another component. Examples of the radical polymerizable component include various compounds, such as (meth)acrylates, (meth)acrylamides, urethane acrylates, epoxy acrylates, polyester acrylates, tris(acryloxyethyl)isocyanurates, maleimides, (meth)acrylic acid, maleic acid, itaconic acid, (meth)acrylaldehyde, N-vinyl-2-pyrrolidone, triallyl isocyanurate, divinyl adipate, vinyltrimethoxysilane, etc. From the viewpoints of availability and ease of handling, (meth)acrylates, (meth)acrylamides, and maleimides are preferred, and urethane acrylates are particularly preferred from the viewpoint of film processing, since they can increase adhesion immediately after curing.

[0025] Specific examples of (meth)acrylates having one (meth)acryloyl group in the molecule include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. , 1,4-cyclohexanedimethylol mono(meth)acrylate, dicyclopentanyl(meth)acrylate, dicyclopentenyl(meth)acrylate, dicyclopentenyloxyethyl(meth)acrylate, benzyl(meth)acrylate, phenol alkylene oxide adduct(meth)acrylate, p-cumylphenol alkylene oxide adduct(meth)acrylate, o-phenylphenol alkylene oxide adduct(meth)acrylate, nonylphenol alkylene oxide adduct(meth)acrylate, 2- Methoxyethyl (meth)acrylate, ethoxyethoxyethyl (meth)acrylate, (meth)acrylate of alkylene oxide adduct of 2-ethylhexyl alcohol, pentanediol mono(meth)acrylate, hexanediol mono(meth)acrylate, diethylene glycol mono(meth)acrylate, triethylene glycol mono(meth)acrylate, tetraethylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, dipropylene glycol mono(meth)acrylate, triethylene glycol mono(meth)acrylate, Propylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, tetrahydrofurfuryl (meth)acrylate, caprolactone-modified tetrahydrofurfuryl (meth)acrylate, (2-ethyl-2-methyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-isobutyl-2-methyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (1,4-dioxaspiro[4,5]decan-2-yl)methyl (meth)acrylate, glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 2-(meth)acryloyloxyethyl isocyanate, allyl (meth)acrylate, N-(meth)acryloyloxyethyl hexahydrophthalimide, N-(meth)acryloyloxyethyl tetrahydrophthalimide, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl succinic acid, ω-carboxy-polycaprolactone mono(meth)acrylate, 2-(meth)acryloyloxyethyl acid phosphate, 3-(meth)acryloyloxypropyl trimethoxysilane, 3-(meth)acryloyloxypropyl dimethoxymethylsilane, 3-(meth)acryloyloxypropyl triethoxysilane, etc.,

[0026] Specific examples of (meth)acrylates having two or more (meth)acryloyl groups in the molecule [hereinafter referred to as "polyfunctional (meth)acrylates"] include neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, cyclohexanedimethylol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, Examples of the di(meth)acrylate include butyl di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tricyclodecane dimethylol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri- or tetra(meth)acrylate, dipentaerythritol penta- or hexa(meth)acrylate, and di(meth)acrylate of hydrogenated bisphenol A, polyethylene glycol (repeating number 8 or more) di(meth)acrylate, polypropylene glycol (repeating number 6 or more) di(meth)acrylate, and di(meth)acrylate of bisphenol A alkylene oxide adduct.

[0027] Specific examples of (meth)acrylamides include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-methylol(meth)acrylamide, N-(3-N,N-dimethylaminopropyl)(meth)acrylamide, methylenebis(meth)acrylamide, ethylenebis(meth)acrylamide, N,N-diallyl(meth)acrylamide, and (meth)acryloylmorpholine.

[0028] Examples of the urethane (meth)acrylates include urethane (meth)acrylates which are reaction products of polyols such as ethylene glycol, 1,4-butanediol, polytetramethylene glycol, neopentyl glycol, polycaprolactone polyol, polyester polyol, polycarbonate diol, or polytetramethylene glycol, organic polyisocyanates such as hexamethylene diisocyanate, alicyclic polyisocyanate, tolylene diisocyanate, xylylene diisocyanate, or 4,4'-diphenylmethane diisocyanate, and hydroxyl group-containing ethylenically unsaturated compounds such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 1,4-butanediol mono(meth)acrylate, an ε-caprolactone adduct of 2-hydroxyethyl (meth)acrylate, or pentaerythritol tri(meth)acrylate. By incorporating urethane acrylate, the adhesiveness immediately after curing can be increased, which is preferable from the viewpoint of film processing.

[0029] Examples of epoxy (meth)acrylates include epoxy (meth)acrylates which are reaction products of polyglycidyl compounds such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenol novolac type epoxy resin, trisphenolmethane type epoxy resin, polyethylene glycol diglycidyl ether, glycerin polyglycidyl ether, and trimethylolpropane polyglycidyl ether with (meth)acrylic acid.

[0030] Examples of polyester acrylates include polyester acrylates such as trimethylolpropane tri(meth)acrylate, trimethylolpropane polyethoxy tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and tripentaerythritol octa(meth)acrylate.

[0031] Examples of tris(acryloxyethyl)isocyanurates include tris(acryloxyethyl)isocyanurate and trisallylisocyanurate.

[0032] Specific examples of maleimides include N-methylmaleimide, N-hydroxyethylmaleimide, N-hydroxyethylcitraconimide, and a urethane reaction product of N-hydroxyethylcitraconimide and isophorone diisocyanate.

[0033] Specific examples of the photoradical polymerization initiator (d) used in the adhesive composition of the present invention include the following compounds.

[0034] 4'-Phenoxy-2,2-dichloroacetophenone, 4'-tert-butyl-2,2-dichloroacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 1-hydroxycyclohexyl phenyl ketone, α,α-diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methyl Acetophenone-based photopolymerization initiators such as propan-1-one, 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methylpropan-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one; benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl benzoin ether-based photoinitiators such as benzoin ether; benzophenone-based photoinitiators such as benzophenone, o-benzoylmethylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, and 2,4,6-trimethylbenzophenone; thioxanthone-based photoinitiators such as 2-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, and 1-chloro-4-propoxythioxanthone; Acylphosphine oxide photoinitiators such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide; oxime ester photoinitiators such as 1,2-octanedione, 1-[4-(phenylthiophenyl)]-, 2-(O-benzoyloxime); camphorquinone, etc.

[0035] The component (d) may be used alone or in combination of two or more depending on the desired performance. When the photoradical polymerization initiator (d) is used, its content is preferably 20 parts by weight or less, more preferably 0.1 to 10 parts by weight, and even more preferably 0.1 to 5 parts by weight, based on the total composition. By setting the content of the photoradical polymerization initiator (d) within the above range, sufficient adhesive strength is obtained and curability is also excellent.

[0036] Furthermore, as long as the effect of the present invention is not impaired, the adhesive composition may contain other additives, such as ion trapping agents, antioxidants, antiaging agents, stabilizers, chain transfer agents, sensitizers, tackifiers, thermoplastic resins, fillers, flow control agents, plasticizers, defoamers, organic solvents, dyes, pigments, treatment agents, and ultraviolet blocking agents. Ion trapping agents include, for example, powdered bismuth-, antimony-, magnesium-, aluminum-, calcium-, titanium-, and mixtures thereof, and other inorganic compounds. Antioxidants include, for example, hindered phenol-based antioxidants. Tackifying resins include, for example, rosins such as rosin acid, polymerized rosin acid, and rosin acid esters, terpene resins, terpene phenol resins, aromatic hydrocarbon resins, aliphatic saturated hydrocarbon resins, and petroleum resins.

[0037] The adhesive composition of the present invention can be produced by stirring and mixing the above-mentioned components according to a conventional method. In this case, heating can be performed if necessary. The heating temperature and time can be appropriately set depending on the composition used, the base material, the purpose, etc., but a temperature of 30 to 80°C for about 30 minutes to 2 hours is preferable.

[0038] The viscosity of the composition is preferably 10 to 1000 mPa·s in terms of excellent coatability onto a substrate.

[0039] The thickness of the adhesive layer of the polarizing plate is preferably in the range of 0.05 to 100 μm. If it is less than 0.05 μm, the adhesive strength is weak. If it exceeds 100 μm, the transmitted light is reduced, the transmitted image is distorted, and the optical properties may be deteriorated. For applications where the optical properties are important, it is preferable to make the thickness as thin as possible within the range where the decrease in adhesive strength is acceptable, since the optical properties are improved by making the thickness thin. It is preferably 5 μm or less, more preferably 2.5 μm or less, even more preferably 1 μm or less, and most preferably 0.5 μm or less. The adhesive of the present invention can be made thin because it can also reduce the viscosity. In addition, in applications where a certain strength is required for the polarizing plate, it is preferable that the adhesive layer is thick. It is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 25 μm or more, and most preferably 50 μm or more. The adhesive of the present invention can be made thick because it can also increase the viscosity.

[0040] [Polarizing plate] The polarizing plate according to the present invention is obtained by laminating a protective film on one or both sides of a polarizer in which a dichroic dye is adsorbed and oriented on a uniaxially stretched polyvinyl alcohol-based resin film. The polyvinyl alcohol-based resin constituting the polarizer is obtained by saponifying a polyvinyl acetate-based resin. Examples of the polyvinyl acetate-based resin include polyvinyl acetate, which is a homopolymer of vinyl acetate, as well as copolymers of vinyl acetate and other monomers copolymerizable therewith. Examples of other monomers copolymerized with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, and unsaturated sulfonic acids. The saponification degree of the polyvinyl alcohol-based resin is usually 85 to 100 mol%, and preferably 98 to 100 mol%. The polyvinyl alcohol-based resin may be further modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes may also be used. The degree of polymerization of the polyvinyl alcohol resin is usually in the range of 1,000 to 10,000, and preferably 1,500 to 10,000.

[0041] A polarizing plate is manufactured through a process including a step of uniaxially stretching such a polyvinyl alcohol-based resin film, a step of dyeing the polyvinyl alcohol-based resin film with a dichroic dye to adsorb the dichroic dye, a step of treating the polyvinyl alcohol-based resin film with the adsorbed dichroic dye with an aqueous boric acid solution, a step of washing with water after the treatment with the aqueous boric acid solution, and a step of laminating a protective film onto the uniaxially stretched polyvinyl alcohol-based resin film with the dichroic dye adsorbed and oriented as a result of the above steps.

[0042] The uniaxial stretching may be performed before dyeing with a dichroic dye, simultaneously with dyeing with a dichroic dye, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing with a dichroic dye, the uniaxial stretching may be performed before the boric acid treatment or during the boric acid treatment. Of course, the uniaxial stretching can be performed in these multiple stages. For the uniaxial stretching, the film may be uniaxially stretched between rolls having different peripheral speeds, or may be uniaxially stretched using a heated roll. The film may be dry-stretched in air, or wet-stretched in a state swollen with a solvent. The stretching ratio is usually about 4 to 8 times.

[0043] To dye a polyvinyl alcohol-based resin film with a dichroic dye, for example, the polyvinyl alcohol-based resin film may be immersed in an aqueous solution containing the dichroic dye. As the dichroic dye, specifically, iodine or a dichroic dye is used.

[0044] When iodine is used as the dichroic dye, a method of dyeing a polyvinyl alcohol resin film by immersing it in an aqueous solution containing iodine and potassium iodide is usually adopted. The content of iodine in this aqueous solution is usually about 0.01 to 0.5 parts by weight per 100 parts by weight of water, and the content of potassium iodide is usually about 0.5 to 10 parts by weight per 100 parts by weight of water. The temperature of this aqueous solution is usually about 20 to 40°C, and the immersion time in this aqueous solution is usually about 30 to 300 seconds.

[0045] On the other hand, when a dichroic dye is used as the dichroic pigment, a method of dyeing a polyvinyl alcohol resin film by immersing it in an aqueous solution containing a water-soluble dichroic dye is usually adopted. The content of the dichroic dye in this aqueous solution is usually about 1×10-3 to 1×10-2 parts by weight per 100 parts by weight of water. This aqueous solution may contain an inorganic salt such as sodium sulfate. The temperature of this aqueous solution is usually about 20 to 80° C., and the immersion time in this aqueous solution is usually about 30 to 300 seconds.

[0046] The boric acid treatment after dyeing with a dichroic dye is carried out by immersing the dyed polyvinyl alcohol-based resin film in an aqueous boric acid solution. The content of boric acid in the aqueous boric acid solution is usually about 2 to 15 parts by weight, preferably about 3 to 8 parts by weight, per 100 parts by weight of water. When iodine is used as the dichroic dye, the aqueous boric acid solution preferably contains potassium iodide. The content of potassium iodide in the aqueous boric acid solution is usually about 2 to 20 parts by weight, preferably 5 to 15 parts by weight, per 100 parts by weight of water. The immersion time in the aqueous boric acid solution is usually about 100 to 1,200 seconds, preferably about 150 to 600 seconds, and more preferably about 200 to 400 seconds. The temperature of the aqueous boric acid solution is usually 50°C or higher, preferably 50 to 85°C.

[0047] The polyvinyl alcohol-based resin film after the boric acid treatment is usually washed with water. The washing is performed, for example, by immersing the boric acid-treated polyvinyl alcohol-based resin film in water. After washing with water, a drying process is performed to obtain a polarizer. The temperature of water in the washing process is usually about 5 to 40°C, and the immersion time is usually about 2 to 120 seconds. The drying process performed thereafter is usually performed using a hot air dryer or a far-infrared heater. The drying temperature is usually 40 to 100°C. The processing time in the drying process is usually about 120 to 600 seconds.

[0048] In this manner, a polarizer made of a polyvinyl alcohol-based resin film on which iodine or a dichroic dye is adsorbed and oriented is obtained. Next, a protective film is attached to one or both sides of this polarizer using the adhesive composition of the present invention.

[0049] The polarizing plate of the present invention can typically be produced by a method including a coating step of applying the adhesive composition of the present invention in an uncured state to a protective film to form an adhesive-coated surface, a lamination step of laminating a polarizer to the adhesive-coated surface of the protective film, and a curing step of curing the adhesive composition.

[0050] As another method for producing a polarizer in the present invention, a method can be adopted in which the adhesive composition of the present invention is dropped between the polarizer and the protective film in an uncured state, and then the two are pressed together while being uniformly spread with a roll or the like, and then the adhesive composition is cured to form an adhesive layer.

[0051] [Coating process] There is no particular limitation on the method of applying the adhesive to the polarizer, and various coating methods can be used, such as a doctor blade, a wire bar, a die coater, a comma coater, and a gravure coater. In addition, since each coating method has its own optimal viscosity range, adjusting the viscosity using a solvent is also a useful technique. For this purpose, a solvent that dissolves the adhesive composition well without reducing the optical performance of the polarizer is used, and there is no particular limitation on the type of solvent. For example, organic solvents such as hydrocarbons represented by toluene and esters represented by ethyl acetate can be used. The thickness of the adhesive layer is usually 100 μm or less, preferably 20 μm or less, and more preferably 10 μm or less. The thinner the adhesive layer, the more the distortion of the polarizing plate is suppressed.

[0052] [Lamination process] When the adhesive composition of the present invention is applied to the protective film, a polarizer is then attached to the adhesive-coated surface. The protective film used in the polarizing plate of the present invention is typically a film having transparency. The protective film is not particularly limited, and specifically, a film of an acetyl cellulose-based resin such as triacetyl cellulose, which is currently most widely used as a protective film for polarizing plates, or a film of a transparent resin having a lower moisture permeability than triacetyl cellulose can be used. From the viewpoint of improving the resistance to moist heat, it is preferable to use a film of a transparent resin having a lower moisture permeability.

[0053] In the polarizing plate of the present invention, typically, a film of an acetyl cellulose-based resin or a film of a transparent resin having a lower moisture permeability than triacetyl cellulose is attached to at least one surface of the polarizer.

[0054] The moisture permeability of the above triacetyl cellulose is approximately 400 g / m 2 When a protective film is applied to both sides of a polarizer, two protective films may be applied stepwise to each side, or both sides may be applied in one step.

[0055] Examples of the acetyl cellulose resin film include the above-mentioned triacetyl cellulose film, as well as diacetyl cellulose film and acetyl butyl cellulose film.

[0056] Examples of transparent resin films having lower moisture permeability than triacetyl cellulose include films of at least one transparent resin selected from amorphous polyolefin resins, polyester resins such as polyethylene terephthalate, acrylic resins, polycarbonate resins, polysulfone resins, and alicyclic polyimide resins. Among them, films made of amorphous polyolefin resins are particularly preferred. Amorphous polyolefin resins usually have polymerization units of cyclic olefins such as norbornene and polycyclic norbornene monomers, and may be copolymers of cyclic olefins and chain olefins. Examples of such amorphous polyolefin resins include thermoplastic saturated norbornene resins. Also, those having polar groups introduced therein are effective. Commercially available amorphous polyolefin resins include "Arton" from JSR Co., Ltd., "ZEONEX" and "ZEONOR" from Nippon Zeon Co., Ltd., and "APO" and "Apel" from Mitsui Chemicals, Inc. When forming a film from an amorphous polyolefin-based resin, a known method such as a solvent casting method or a melt extrusion method is appropriately used for film formation. These amorphous polyolefin-based resin films have a film thickness of about 300 g / m 2 / Has a moisture permeability of less than 24hr.

[0057] In the present invention, when a protective film is attached to both sides of the polarizer, the protective films attached to one side and the other side of the polarizer may be of the same type or different types. When different types of protective films are attached to both sides of the polarizer, for example, a film of an acetyl cellulose resin can be used as one protective film, and a film of a transparent resin having a lower moisture permeability than triacetyl cellulose can be used as the other protective film. In the past, wet lamination using an adhesive with water as a solvent was used to bond the acetyl cellulose protective film to the polarizer, but in this case, a long and large drying oven is required. On the other hand, in the present invention, no drying oven is required at all. As advantages in this case, as described above, there is no need for capital investment in a drying oven, the polarizer and / or the adhesive layer do not deteriorate due to heat, and curling can be suppressed.

[0058] In addition, when a protective film having a relatively high moisture permeability, such as an acetyl cellulose-based resin film, is provided on one surface of the polarizer, an adhesive other than the adhesive composition of the present invention, such as a polyvinyl alcohol-based adhesive, may be used on the bonding surface between the protective film and the polarizer.

[0059] The surface of the protective film to be attached to the polarizer may be subjected to an easy-adhesion treatment such as saponification treatment, corona treatment, primer treatment, anchor coating treatment, plasma treatment, flame treatment, etc., prior to attachment to the polarizer. In addition, the surface of the protective film opposite to the surface to be attached to the polarizer may have various treated layers such as a hard coat layer, an antireflection layer, an antiglare layer, etc. The thickness of the protective film is usually in the range of about 5 to 300 μm, preferably 10 to 200 μm, and more preferably 10 to 100 μm.

[0060] [Curing process] As described above, after the polarizer and the protective film are bonded to each other via the uncured adhesive composition, the adhesive composition is cured by irradiation with active energy rays, and the protective film is fixed onto the polarizer.

[0061] The light source of the active energy ray is not particularly limited, but is preferably an active energy ray having an emission distribution at a wavelength of 400 nm or less, and specifically, is preferably a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a chemical lamp, a black light lamp, a microwave excited mercury lamp, a metal halide lamp, etc. The light irradiation intensity of the adhesive composition is appropriately determined depending on the composition of the adhesive composition, and is not particularly limited, but is preferably an irradiation intensity of 0.1 to 6000 mW / cm in a wavelength region effective for activating a polymerization initiator. 2 It is preferable that the irradiation intensity is 0.1 mW / cm 2 If the reaction time is not too long, the power consumption will be 6000mW / cm 2When the light irradiation time is less than 10,000 mJ / cm, the epoxy resin is less likely to turn yellow due to the heat radiated from the light source and the heat generated during curing of the adhesive composition, and the polarizer is less likely to deteriorate. The light irradiation time for the adhesive composition is controlled for each adhesive composition to be cured and is not particularly limited. However, the integrated light amount, which is expressed as the product of the irradiation intensity and the irradiation time, is preferably 10 to 10,000 mJ / cm. 2 It is preferable that the integrated light amount on the adhesive composition is set to 10 mJ / cm. 2 When the irradiation amount is more than 10,000 mJ / cm, a sufficient amount of active species derived from the polymerization initiator can be generated to ensure the curing reaction. 2 When it is equal to or less than this, the irradiation time is not too long and good productivity can be maintained.

[0062] When the adhesive composition is cured by irradiation with active energy rays, it is preferable to perform the curing under conditions that do not deteriorate the various functions of the polarizing plate, such as the degree of polarization, transmittance, and hue of the polarizer, and the transparency of the protective film.

[0063] The curing step may be carried out prior to the laminating step. In this case, the adhesive composition cured in the curing step is laminated to the polarizer or the protective film, thereby fixing the protective film onto the polarizer. EXAMPLES

[0064] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. In the examples, "parts" means parts by weight.

[0065] (Preparation of Adhesive Composition) [Example 1] 28.8 parts of 4-hydroxybutyl acrylate manufactured by Osaka Organic Chemical Industry Co., Ltd. was added as component (a) and 3.8 parts of Omnirad TPO H manufactured by IGM as component (d) were added and stirred at 25°C for 1 hour, and then 67.3 parts of 24A-100 manufactured by Asahi Kasei Corporation was added as component (b) and stirred at 25°C for 5 minutes to obtain an adhesive composition.

[0066] [Examples 2 to 13] An adhesive composition was obtained in the same manner as in Example 1, except that the formulation was changed to that shown in Table 1.

[0067] [Example 14] 33.3 parts of 4-hydroxybutyl acrylate manufactured by Osaka Organic Chemical Industry Co., Ltd. as component (a), 8.8 parts of KAYARAD PET30 manufactured by Nippon Kayaku Co., Ltd. as component (c), and 3.5 parts of Omnirad TPO H manufactured by IGM as component (d) were added and stirred at 25°C for 1 hour, and then 54.4 parts of 24A-100 manufactured by Asahi Kasei Corporation was added as component (b) and stirred at 25°C for 5 minutes to obtain an adhesive composition.

[0068] [Examples 15 to 19] An adhesive composition was obtained in the same manner as in Example 14, except that the formulation was changed to that shown in Table 2. [Example 20] 36.9 parts of 4-hydroxybutyl acrylate manufactured by Osaka Organic Chemical Industry Co., Ltd. as component (a) and 9.2 parts of KAYARAD UX-0937 manufactured by Nippon Kayaku Co., Ltd. as component (c) were added and stirred at 60°C for 30 minutes, then cooled at room temperature for 30 minutes, and then 3.8 parts of Omnirad TPO H manufactured by IGM was added as component (d) and stirred at 25°C for 1 hour, and then 50.0 parts of 24A-100 manufactured by Asahi Kasei Corporation was added as component (b) and stirred at 25°C for 5 minutes to obtain an adhesive composition.

[0069] [Examples 21 to 31] Except for changing the formulation as shown in Tables 3 and 4, the same preparation as in Example 20 was carried out to obtain adhesive compositions.

[0070] [Comparative Examples 1 to 4] An adhesive composition was obtained in the same manner as in Example 1, except that the components were changed to those shown in Table 4.

[0071] [Comparative Example 5] 97.6 parts of CELLOXIDE 2021P manufactured by Daicel Corporation, which is an alicyclic epoxy compound, and 2.4 parts of CPI-110P manufactured by San-Apro Co., Ltd., which is a photoacid generator, were added and stirred at 25° C. for 4 hours to obtain an adhesive composition.

[0072] (Fabrication of polarizing element) Based on the description in Example 1 of JP-A-11-218611, the following dyes 1 to 4 were prepared, and dyes 1 to 4 and Glauber's salt were dissolved in water to prepare a dyeing solution. Dye 1: CIDirect Orange 39 (Kayafect Orange G, manufactured by Nippon Kayaku Co., Ltd.) was used. Dye 2: CI Direct Red 81 (Red 4BL, manufactured by Nippon Chemical Industry Co., Ltd.) was used. Dye 3: The dye having the chemical formula described in JP-A-11-218611 was synthesized according to the same publication.

[0073] [ka]

[0074] Dye 4: A dye having the chemical formula disclosed in Example 38 of JP-A-60-156759 was synthesized according to the same publication.

[0075] [ka]

[0076] Next, a PVA-based resin film (VF-PS#7500 manufactured by Kuraray Co., Ltd.) was immersed in water while being uniaxially stretched to swell, and then immersed in the dyeing solution and stretched with an aqueous boric acid solution to orient the dye in the resin film. The uniaxial stretching ratio from swelling to boric acid treatment was 4 to 5 times in total. After stretching, the film was dried in a dryer at 70°C for 3 minutes while maintaining tension to form a polarizing element. The obtained polarizing element exhibited a grayish color, and when measured using a spectrophotometer UH-4150 manufactured by Hitachi High-Tech Science Co., Ltd., its optical characteristics were Ys=60.5%, Py=47.7%, and the hue in the L*a*b* color space was L*s=82.1, a*s=0.4, and b*s=-0.2.

[0077] (Manufacture of polarizing plates) A 50 μm thick amorphous polyolefin resin film (trade name Zeonor ZF14, manufactured by Zeon Corporation, hereafter referred to as “ZF14”) was subjected to a corona treatment (AGF-B10 manufactured by Kasuga Electric Co., Ltd., output 0.3 kW, speed 3 m / min) as an adhesion enhancing treatment. Then, the adhesive compositions shown in Tables 1 to 4 were applied to the corona-treated surface of "ZF14" using a bar coater. After laminating a polarizer onto this, it was cured with a high-pressure mercury lamp (HX4000L manufactured by Harrison Toshiba Lighting Co., Ltd.) at 120 W, 5 m / min, and 1 pass to obtain a laminate film. Next, the same adhesive composition was applied onto the corona-treated "ZF14" using a bar coater, and the polarizer side of the obtained laminate film was laminated, followed by curing with the high-pressure mercury lamp under the same conditions to obtain a polarizing plate. Finally, the obtained polarizing plate was aged in a dryer at 35° C. for 7 days in order to react the hydroxyl group and the isocyanate group in the adhesive layer.

[0078] The obtained adhesive compositions and polarizing plates were used to carry out the following evaluations, and the results are shown in Tables 1 to 4. (viscosity measurement) The viscosity of the adhesive composition was measured in a 25° C. environment using an E-type viscometer. (Thickness measurement) The thickness of the polarizing plate was measured using a high-precision thickness measuring instrument HKT-1202 manufactured by Fujiwork Co., Ltd., and the thickness of the adhesive layer was calculated using the measured value and the thicknesses of the polarizer and protective film. (High temperature and humidity resistance evaluation) The polarizing plate cut into a size of 50 mm×50 mm was placed in a thermohygrostat at 85° C. and 85% RH for 1000 hours, and the state of the polarizing plate end surface was evaluated according to the following criteria. ◯: The polarizer was not peeled off from the protective film, and the protective film alone was not visually observed at the edge portions. ×: The polarizer was peeled off from the protective film and shrunk, and only the protective film was observed at the edge portion by visual inspection.

[0079] <Coloring evaluation> The polarizing plate was placed in a thermohygrostat at 85° C. and 85% RH and a dryer at 105° C. for 1000 hours, and then taken out and visually evaluated for its hue. The evaluation criteria were as follows: (Evaluation Criteria) 〇: Colorless (no browning of polarizer) ×;Yellow~brown (Adhesion evaluation) A cutter blade was inserted between the polarizer and the protective film of the polarizing plate, and the adhesion was evaluated according to the following criteria. ◎: Substrate destruction (cutter blade cannot enter) ○: Base material destruction (cutter blade penetrates) ×: Can be peeled off by hand (Adhesion evaluation immediately after curing) Immediately after the adhesive composition was cured by the high pressure mercury lamp, the polarizer, adhesive layer, and protective film were peeled off by hand to evaluate their adhesion, and the adhesion was evaluated according to the following criteria. ◎: Strong resistance is felt when peeling off ○: Resistance is felt when peeling off ×: Easily peeled off

[0080] [Table 1]

[0081] [Table 2]

[0082] [Table 3]

[0083] [Table 4]

[0084] As can be seen from Tables 1 to 4, Examples 1 to 31 using the present invention showed high resistance to high temperature and high humidity, and also showed high adhesion. Furthermore, since none of the adhesive compositions used in the present examples contained acid, browning due to polyenation was observed even after the durability test. On the other hand, in all of Comparative Examples 1 to 4, in which the isocyanate compound was 20% or less, peeling occurred between the protective substrate and the polarizer after the high temperature and high humidity durability test, and the polarizer showed low resistance to high temperature and high humidity. Furthermore, in Comparative Example 5, which used an adhesive composition consisting of a photoacid generator and an epoxy compound, discoloration of the polarizer occurred due to polyenation after the durability test due to the effect of the generated acid.

[0085] As described above, by using the adhesive composition of the present invention, it is possible to provide an adhesive composition and a polarizing plate which have high resistance to high temperatures and high humidity, high adhesion, and which do not cause discoloration of the polarizer due to polyenation.

Claims

1. It is made of a polyvinyl alcohol resin film on which iodine or a dichroic dye is adsorbed and oriented. An adhesive used for bonding a polarizer and a protective film, comprising, per 100 parts by weight of the adhesive composition, (a) a hydroxy group-containing (meth)acrylate content of 25% by weight or more and 65% by weight or less; and (b) the isocyanate compound is more than 20% by weight and not more than 70% by weight; An adhesive composition comprising:

2. 2. The adhesive composition according to claim 1, further comprising a photopolymerization initiator.

3. 3. The adhesive composition according to claim 1, wherein the isocyanate compound is at least one selected from the group consisting of an isocyanurate of hexamethylene diisocyanate, an adduct of hexamethylene diisocyanate, and a biuret of hexamethylene diisocyanate.

4. 3. The adhesive composition according to claim 1, further comprising a urethane acrylate.

5. A polarizing plate comprising a polyvinyl alcohol resin film having iodine or a dichroic dye adsorbed and oriented thereon, and a protective film attached to one or both sides of the polyvinyl alcohol resin film using the adhesive composition according to claim 1 or 2.

6. 6. The polarizing plate according to claim 5, wherein the protective film is a film of at least any one transparent resin selected from the group consisting of amorphous polyolefin-based resins, polyester-based resins, acrylic-based resins, polycarbonate-based resins, polysulfone-based resins, and alicyclic polyimide-based resins, bonded to at least one surface of the polarizer.

Citation Information

Patent Citations

  • Polarizing film for liquid crystal display

    JP1994051117A

  • Polarizing plate, its manufacturing method, optical member, and liquid crystal display device

    JP2004245925A

  • Photocurable adhesive composition and polarizing plate using the same

    JP2010008928A